Autoimmune rheumatic diseases in women with coronary microvascular dysfunction: a report from the Women's Ischemia Syndrome Evaluation—Coronary Vascular Dysfunction (WISE-CVD) project - Chen, Melanie T.; Chang, Joseph; Manchanda, Ashley S.; Cook-Wiens, Galen; Shufelt, Chrisandra L.; Anderson, R. David; Petersen, John W.; Naik, Dhaval R.; Thomson, Louise E. J.; Berman, Daniel S.; Handberg, Eileen M.; Pepine, Carl J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: While autoimmune rheumatic diseases (ARDs) have been linked with coronary microvascular dysfunction (CMD), the relationship between ARD and CMD in women with signs and symptoms of ischemia and no obstructive arteries (INOCA) are not well described. We hypothesized that among women with CMD, those with ARD history have greater angina, functional limitations, and myocardial perfusion compromise compared to those without ARD history. Methods: Women with INOCA and confirmed CMD by invasive coronary function testing were included from the Women’s Ischemia Syndrome Evaluation-Coronary Vascular Dysfunction (WISE-CVD) project (NCT00832702). Seattle Angina Questionnaire (SAQ), Duke Activity Status Index (DASI), and cardiac magnetic resonance myocardial perfusion reserve index (MPRI) were collected at baseline. Chart review was performed to confirm self-reported ARD diagnosis. Results: Of the 207 women with CMD, 19 (9%) had a confirmed history of ARD. Compared to those without ARD, women with ARD were younger (p=0.04). In addition, they had lower DASI-estimated metabolic equivalents (p=0.03) and lower MPRI (p=0.008) but similar SAQ scores. There was a trend towards increased nocturnal angina and stress-induced angina in those with ARD (p=0.05 for both). Invasive coronary function variables were not significantly different between groups. Conclusions: Among women with CMD, women with a history of ARD had lower functional status and worse myocardial perfusion reserve compared to women without ARD. Angina-related health status and invasive coronary function were not significantly different between groups. Further studies are warranted to understand mechanisms contributing to CMD among women with ARDs with INOCA.